Crab Diets Differ Between Adjacent Estuaries and Habitats Within a Sheltered Marine Embayment - Campbell, Theo I.; Tweedley, James R.; Johnston, Danielle J.; Loneragan, Neil R. (Frontiers in Marine Science, 2021)
Portunid crabs contribute to significant commercial and recreational fisheries globally and are commonly fished in estuaries and/or marine embayments, which are amongst the most anthropogenically influenced of all aquatic ecosystems. Portunus armatus were collected seasonally between April 2016 and February 2017 from five locations across three systems in south-western Australia. The dietary composition of crabs was quantified and compared between two estuaries (Peel-Harvey and Swan-Canning) and a sheltered marine embayment (Cockburn Sound) containing three distinct habitats: shallow seagrass, shallow sand and deep sand. A total of 630 crabs were collected in the early pre-moult and inter-moult stage and measured, sexed, moult staged and the stomachs removed. Stomachs of 429 P. armatus contained food items, with large volumes of bivalves (both live and dead shell), polychaetes, and crustaceans (e.g. amphipods, small decapods), with teleosts, echinoderms and plant material (seagrass, algae) present in smaller volumes. Multivariate analyses showed dietary composition varied significantly among locations and seasons, with greater location differences. Diets were most distinct in Cockburn Sound seagrass due to greater volumes of decapods and teleosts and smaller volumes of bivalve shell. Crabs from both estuaries consumed greater quantities of bivalves than those from Cockburn Sound. Seasonal differences were greatest between winter and summer in both estuaries, with consumption of large bivalves greatest in summer, whereas consumption of small bivalves and bivalve shell in the Peel-Harvey and polychaetes and other crustaceans in the Swan-Canning, were greatest in winter. The number of prey taxa consumed in summer was greater in summer than winter in both estuaries. Variations in prey availability are the likely cause of these location and seasonal differences in diet. The summer diet in the Peel-Harvey Estuary in the current study was compared to that 20 years previous. Currently, crabs consume smaller volumes of high-calorie prey, i.e. polychaetes, small bivalves and teleosts and instead ingest greater proportions of calcareous material than previously. This marked shift in dietary composition parallels the documented changes in benthic macroinvertebrates in the Peel-Harvey Estuary. Overall, prey availability appears to be the major factor influencing the spatial and temporal differences in P. armatus diets in south-western Australia.